2022
DOI: 10.1039/d2ra01040b
|View full text |Cite
|
Sign up to set email alerts
|

Thiosemicarbazide functionalized carbon quantum dots as a fluorescent probe for the determination of some oxicams: application to dosage forms and biological fluids

Abstract: Highly fluorescent nitrogen and sulfur doped carbon quantum dots were synthesized via hydrothermal process using citric acid and thiosemicarbazide. The dots had an emission band at 415 nm (λex = 345 nm). The polarity of the studied drugs affects the method’s sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…In addition, SN-CQDs produced strong blue fluorescence when exposed to UV light, and the solution remained stable for about two weeks without alteration. The amino, carbonyl, and hydroxyl groups were found to be responsible for the SN-CQDs' excellent hydrophilicity and high fluorescence 41 , 52 .
Figure 2 Fluorescence emission spectrum of SN-CQDs at 430 nm after excitation at 360 nm.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SN-CQDs produced strong blue fluorescence when exposed to UV light, and the solution remained stable for about two weeks without alteration. The amino, carbonyl, and hydroxyl groups were found to be responsible for the SN-CQDs' excellent hydrophilicity and high fluorescence 41 , 52 .
Figure 2 Fluorescence emission spectrum of SN-CQDs at 430 nm after excitation at 360 nm.
…”
Section: Resultsmentioning
confidence: 99%
“…Due to their excellent photo-physical properties, high quantum yields, superior solubility, low toxicity, lowcost, and eco-friendly nature with strong fluorescence emission, carbon-quantum-dots (CQDs)-have piqued theinterest-of researchers in a variety of fields [34][35][36][37] . The top-down 38,39 and bottom-up 40 approaches-for synthesis-of CQDs have both been reported 41 . Larger carbon structures are divided into smaller ones during the top-down processes used to manufacture CQDs, such as electrochemical oxidation and laser ablation, which resulted in low yields and high costs.…”
mentioning
confidence: 99%
“…To ensure the change in lifetime of the CQDs, lifetime study of both CQDs and CQDs+H2O were performed and it was come spectroscopic results confirmed that the quenching process is dynamic one. [70][71][72][73] FRET Process: It is a phenomenon that occurs between the excited state of the CQDs and the ground state of the quencher which may be organic molecules or inorganic analytes. [74] This phenomenon is applied in huge scale in different fields to detect various organic molecules, biologically important molecules, pesticides or inorganic metal ions which may be very important in sense of toxicity.…”
Section: Static Quenchingmentioning
confidence: 99%
“…For the purpose of determining TNX in pharmaceutical formulations, a few high-performance thin-layer chromatography (HPTLC) methods were also published. ,, An HPTLC method has also been reported to determine TNX in combination with piroxicam, celecoxib, and rofecoxib in the whole human blood and urine . Some voltammetry techniques were also used to detect TNX in dosage forms. , Some other approaches such as potentiometric, polarographic, indirect flow-injection spectrophotometry, reverse flow-injection method, fluorescence probe, colloidal gold strip sensor, and quantum dots as fluorescence probe have also been utilized to determine TNX, either alone or in combination with other NSAIDs in pharmaceutical preparations.…”
Section: Introductionmentioning
confidence: 99%